The need for a paradigm shift in the development of military exoskeletons. Issue 1 (2nd January 2022) - Mudie, Kurt; Billing, Daniel; Garofolini, Alessandro; Karakolis, Thomas; LaFiandra, Michael
ABSTRACT: An exoskeleton is a body-worn mechanical device designed to work in concert with the user to enhance human capabilities. For the dismounted close combatant, an exoskeleton could be worn whilst performing a variety of complex tasks and duties. As such, there is a requirement for the human and the exoskeleton to readily adapt to different movements in different contexts. There have been many attempts to design an exoskeleton to improve the performance of the complex adaptive human system with limited success. Despite a vast investment in time and resources, exoskeletons have not yet been adopted for operational use by military leadership for use by the dismounted close combatant as they are yet to demonstrate substantive augmentation to individual warfighter and collective team capability. We argue that a major limitation of current exoskeleton systems is their inability to concurrently adapt to the user, task and environment. Unless a device can meet this requirement, it is unlikely to offer a comparative benefit to the dismounted close combatant. This paper will present the state of the art of current exoskeleton technology, and recommend future research necessary to reach an acceptable standard of augmentation and thereby lead to widespread adoption.